PENGARUH PEMBIAYAAN MUDHARABAH TERHADAP TINGKAT RETURN ON EQUITY(ROE)PADA BANK SYARIAH YANG TERDAFTAR DI BANK INDONESIA - Mahmudin Mahmudin (The Asia Pacific Journal Of Management Studies, 2018)
This study aims to determine whether there is an influence of Mudharabah Financing on Return On Equity (ROE) on Islamic banks registered at Bank Indonesia. In this research, the independent variable is Mudharabah financing income, while the dependent variable is Return on Equity (ROE).This type of research used in this research is a descriptive study with a quantitative approach. Data analysis techniques in this study used the Normality Test, Simple Regression Equation Test, Correlation Coefficient Test, Determination Analysis, and Significant Analysis (t test).The results of this study indicate that mudharabah financing has a significant influence on Islamic banks in Bank Indonesia for the period 2013-2017. The t test results obtained a significant value of 0.031 that the significance value is smaller than the error level of 0.05, which means that when net income falls and capital rises, mudharabah financing at Islamic banks will increase. Return On Equity (ROE) has a significant influence on Islamic banks in Bank Indonesia for the period 2013-2017. Evidenced by the regression coefficient states that each change in mudharabah financing by one unit then the Return On Equity (ROE) will increase by 0.019. Mudharabah Financing has a significant effect on Return On Equity in Islamic Banks registered with Bank Indonesia for the 2013-2017 Period